STAT3 is a biologically relevant therapeutic target in H3K27M-mutant diffuse midline glioma. Issue 10 (9th April 2022) - Zhang, Liang; Nesvick, Cody L; Day, Charlie A; Choi, Jonghoon; Lu, Victor M; Peterson, Timothy; Power, Erica A; Anderson, Jacob B; Hamdan, Feda H; Decker, Paul A; Simons, Renae; Welby, John P; et al.
Abstract: Background: H3K27M-mutant diffuse midline glioma (DMG) is a lethal brain tumor that usually occurs in children. Despite advances in our understanding of its underlying biology, efficacious therapies are severely lacking. Methods: We screened a library of drugs either FDA-approved or in clinical trial using a library of patient-derived H3K27M-mutant DMG cell lines with cell viability as the outcome. Results were validated for clinical relevance and mechanistic importance using patient specimens from biopsy and autopsy, patient-derived cell lines, inhibition by gene knockdown and small molecule inhibitors, and patient-derived xenografts. Results: Kinase inhibitors were highly toxic to H3K27M-mutant DMG cells. Within this class, STAT3 inhibitors demonstrated robust cytotoxic activity in vitro. Mechanistic analyses revealed one form of activated STAT3, phospho-tyrosine- 705 STAT3 (pSTAT3), was selectively upregulated in H3K27M-mutant cell lines and clinical specimens. STAT3 inhibition by CRISPR/Cas9 knockout, shRNA or small molecule inhibition reduced cell viability in vitro, and partially restored expression of the polycomb repressive mark H3K27me3, which is classically lost in H3K27M-mutant DMG. Putative STAT3-regulated genes were enriched in an H3K27M-knockout DMG cell line, indicating relative gain of STAT3 signaling in K27M-mutant cells. Treatment of patient-derived intracranial xenografts with WP1066, a STAT3 pathway inhibitor currently in clinical use for pediatric brain tumors, resulted in stasis of tumor growth, and increased overall survival. Finally, pSTAT3(Y705) was detected in circulating plasma extracellular vesicles of patients with H3K27M-mutant DMG. Conclusions: STAT3 is a biologically relevant therapeutic target in H3K27M-mutant DMG. STAT3 inhibition should be considered in future clinical trials.